New experimental approaches enabling the continuous monitoring of gas species in hydrothermal fluids - Giroud, Sébastien; Tomonaga, Yama; Brennwald, Matthias S.; Takahata, Naoto; Shibata, Tomo; Sano, Yuji; Kipfer, Rolf (Frontiers in Water, 2023)
Hot thermal fluids flow through the Earth's crust and carry valuable information about the deep subsurface. The monitoring of natural tracers transported in geothermal fluids, such as gases or ions, are relevant to better understand the geological processes in the Earth's subsurface and their relation to deep fluid dynamics. Recently developed technologies (e.g., portable gas-equilibrium membrane-inlet mass spectrometry, Brennwald et al., 2016) allow the continuous monitoring of gaseous species at a much higher temporal resolution than the sampling procedures commonly used, based on a few individual samples. However, the monitoring of gas species from hot thermal fluids still poses experimental challenges tied to unwanted water vapor condensation in the headspace of the separation module, which irremediably leads to clogging (e.g., of the connective capillaries) and failure of the detection device. In this contribution, we present two new experimental methods that provide suitable technical conditions to measure geothermal gases, even at high fluid temperature, using a portable gas analyzer. The first method was deployed on the thermal waters of Lavey-les-Bains (Vaud, Switzerland), and the results are reported for October 2021. The second method was used in Beppu (Oita Prefecture, Japan), and the results for April 2018 are presented. Our results show that at both sites, our methods provide continuous measurements of gaseous species in hot thermal waters. Furthermore, they show that the variability of gas emanation from the two sites can only be adequately described by measurements with high temporal resolution, which both methods allow.